Making state circular economy parks work for Indian states (Part 2): An economic analysis using the ICRIER's Sampada WSUT model - Amrita Goldar; Sajal Jain; Ritika Verma; Kartik Nair (Indian Council for Research on International Economic Relations (ICRIER), 2024)
Recycling activities remain at a nascent stage in the country. While the environmental benefits of recycling are well-established, there are several macroeconomic benefits like employment creation. There is an essential need to focus on waste management policies and measures that can aid an effective functioning of the entire waste management system in the country. In line with this perspective, this paper attempts to assess the macroeconomic gains of the proposed Integrated Resource Recovery Park (IRRP) in the state of Rajasthan using the ICRIER Sampada Waste Supply-Use Table (WSUT) model. The WSUT model includes (a) standard monetary input-output table elements, (b) waste generation by intermediate sectors, waste treatment sectors, and final demand sectors, and finally, (c) waste treated by waste treatment methods. These are used to calculate the Leontief inverse of the WSUT. This, when pre-multiplied by changes in the final demand sector, provides the total effects. The analysis highlights direct and indirect benefits in terms of enhanced economic activity and job creation. The ICRIER Sampada WSUT model assesses the direct and indirect impacts of waste management policies and consumption patterns on various macroeconomic parameters. The model incorporates data for monetary transaction values and physical quantities of waste flows, making it capable of accurately evaluating all stages of the consumption process, including purchase, use, and disposal. It provides a comprehensive view of Rajasthan's economy and waste flows in the form of a 47 by 47 matrix, which includes thirty-seven intermediate sectors, four waste treatment technologies (incineration, composting, landfill, and material recovery process), and six waste types (municipal solid waste - dry waste, wet waste, inert waste; hazardous waste; bio-medical waste; and plastic waste). The results highlight that the additional waste treatment undertaken by plants located in the park will result in gains across other linked sectors. An additional treatment of 2.68 lakhs metric tonne per annum (MTPA) of waste, or 5.5 percent of the total waste treated in the state, could lead to additional economic activity of INR 169.48 crores annually for the state. Pulling all the elements together leads to the derivation of the indirect employment that the IRRP in its first phase could lead to. The indirect effects of the park (in terms of its trickledown effects on employment) could be as much as 45 percent of direct effects.
Keywords: Q53; Q52; C67; 330; Circular economy; Economic modelling; Waste management